Psychometric Validation of a Multidimensional Learning Readiness Instrument Following Indonesia’s Free Nutritious Meal Program - Darwis Darwis; Sudirman Sudirman; A Rahim; Abdul Kadir Djailani (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
This study aimed to validate a multidimensional learning readiness instrument within the context of Indonesia's Free Nutritious Meal Program (MBG) using Confirmatory Factor Analysis (CFA). The instrument measured five dimensions: School Participation, Learning Concentration, Learning Energy, Psychological Readiness, and Academic Readiness. Data were collected from 366 students and analyzed using the Robust Maximum Likelihood estimator in R. One indicator (A3) was removed due to low factor loading, resulting in a revised 19-indicator measurement model. The final CFA model demonstrated acceptable goodness-of-fit indices (chi-square = 294.356, df = 142, chi-square/df = 2.07, CFI = 0.944, TLI = 0.933, RMSEA = 0.054, SRMR = 0.042). Convergent validity, discriminant validity, and composite reliability generally supported the psychometric adequacy of the instrument. The findings suggest that the proposed instrument may serve as a useful multidimensional measurement tool for evaluating students' learning readiness within school feeding contexts.